The Impact of Job Characteristics toward Turnover Intentions Mediated by Employee Job Satisfaction in the Restaurant and Café Industry in Surabaya - Beatrice Graciela Khongrad (iBuss Management, 2020)
Restaurant industry is one of Indonesia’s most promising sectors that are currently being appreciated as it is the biggest contributor to Indonesia’s tourism sector. The emotion, attitude, expectation, and view that the employees have about their position and job are important antecedents of the way employees perform at the workplace in which the emotion and behavior are influenced by situational factors refers to job characteristics. The employees might feel dissatisfied with their job due to poor management or even not engaging and unchallenging jobs. As a result of the dissatisfaction, the employees will have an impact in business that can range from low productivity, poor customer service and high turnover. Thus, the researcher would like to know the impact of the relationship between the job characteristics’ core dimensions (skill variety, task identity, task significance, autonomy, and feedback) toward turnover intentions which is mediated by employee job satisfaction.This research has collected the data from 100 eligible respondents in which the collected data have passed the validity, reliability, and BLUE classical assumption tests. The collected data were processed further through multiple linear regression with path analysis and Sobel test. The findings show that skill variety, task identity, task significance, and feedback have a significant influence on turnover intentions. However, employee job satisfaction only mediates the relationship between task significance toward turnover intentions and feedback toward turnover intentions. Keywords: Turnover Intentions, Job Characteristics, Mediation effect of Employee Job Satisfaction, Restaurant and Café Industry